2016
DOI: 10.1063/1.4943097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simple solutes on the long range dipolar correlations in liquid water

Abstract: Intermolecular correlations in liquid water at ambient conditions have generally been characterized through short range density fluctuations described through the atomic pair distribution functions. Recent numerical and experimental results have suggested that such a description of order or structure in liquid water is incomplete and there exist considerably longer ranged orientational correlations in water that can be studied through dipolar correlations. In this study, using large scale classical, atomistic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Finally, let us note that in keeping with the well-established observations that ionic solutes exert a long-range effect on the dipolar correlations in liquid water that goes beyond the simple structure-making and -breaking concept, and that the cross-correlations in the solute–solvent dynamics must include the second hydration shell to fully explain the terahertz spectra of salt solutions, we observe a distinct pattern of both anti- and cross-correlations of molecular dipoles beyond the first hydration shell. These correlations, although of weak intensity, are already well-documented in the case of F – and also Cl – . , As seen in Figure , for the chloride anion, this weaker modulation of the dipolar coupling falls entirely within the limits of the second hydration shell.…”
Section: Results and Discussionsupporting
confidence: 77%
“…Finally, let us note that in keeping with the well-established observations that ionic solutes exert a long-range effect on the dipolar correlations in liquid water that goes beyond the simple structure-making and -breaking concept, and that the cross-correlations in the solute–solvent dynamics must include the second hydration shell to fully explain the terahertz spectra of salt solutions, we observe a distinct pattern of both anti- and cross-correlations of molecular dipoles beyond the first hydration shell. These correlations, although of weak intensity, are already well-documented in the case of F – and also Cl – . , As seen in Figure , for the chloride anion, this weaker modulation of the dipolar coupling falls entirely within the limits of the second hydration shell.…”
Section: Results and Discussionsupporting
confidence: 77%
“…3(b) is to lower the dipole-dipole interaction energy [65]. Moreover, by examining the inset of it has a non vanishing tail even at 75Å [70,76]. However, in order to have a one to one comparison with the experiment and to precisely determine the range at which h D decays to zero, it requires a very large simulation box (at least 10 nm) [69], which is computationally expensive from AAMD simulations.…”
Section: A Bulkmentioning
confidence: 99%
“…35,36 Another example is that Na + is essential to regulate blood pressure but toxic at a high intracellular concentration, whereas K + is not toxic and serves as the major intracellular monovalent ion. 37 Although some recent molecular dynamics studies [38][39][40][41] have reported ion-induced water ordering over nanoscale distances, there is no molecularlevel experimental evidence for long-range specific ion effects on the bulk water structure. An overarching molecular model based on combined experimental data and theory that explains how specific ion effects extend from the first few hydration shells of ions to the bulk water network and lead to macroscopic effects in the bulk properties of electrolyte solutions is still lacking.…”
Section: Introductionmentioning
confidence: 99%